FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAKIF TENTANG WAKAF UANG - Ahmad Nizar (Faculty of Economic and Business, 2014)
The research was motivated by the fact that a wide gap between the realization of cash waqf accumulated and the calculation of cash waqf potential in Indonesia is still wide open. Based on the previous research, one reason influencing the sluggish of cash waqf implementation is people's perception on the cash waqf. Therefore, it is necessary to analyze the factors that influence perceptions of waqif on cash waqf.This research was a kind of descriptive-correlational research that seeked the relationship between education level, income level, mazhab and the information media of cash waqf as independent variables and perceptions of waqif on cash waqf as the dependent variable. Based on data analysis, it was known that from the four independent variables tested, the levels of education have a greater probability in comparison with other variables (income level, mazhab, media information) and it is statistically significant.DOI: 10.15408/ess.v4i1.1953